Effect of Autogenic Relaxation on Blood Pressure Reduction in Elderly Patients with Hypertension - Pipin Sumantrie; Martalina Limbong (Science Midwifery, 2020)
Hypertension is still one of the major health problems in public health in developed countries. Hypertension can be treated with pharmacological and nonpharmacological treatments. One of nonpharmacology treatment is autogenic relaxation to hypertension blood pressure. Objective to determine whether autogenic relaxation can reduce hypertension blood pressure. This was a pre-experimental study with pre and post design, The population of all elderly with hypertension, the ware 10 elderly purposive sampling. Autogenic relaxation techniques are carried out using guidelines for relaxation techniques performed by nurses who have the ability to do relaxation techniques. Independent t-test ware used for data analysis. The result of the analysis showed that there was a change of mean pressure between before and after autogenic relaxation therapy with significant systole value at p - value = 0,00 (α <0,05) and diastol significant value at p - value = 0,00 ( α <0.05) so that there is an autogenic relaxation effect on the decrease in blood pressure in the elderly patients with hypertension. Seeing the results of this study then this autogenic relaxation therapy can be used as an alternative therapy in treating blood pressure problems in elderly or parents in addition to treatment therapy.